2016
DOI: 10.1177/0261927x15619199
|View full text |Cite
|
Sign up to set email alerts
|

The Words for Disgust in English, Korean, and Malayalam Question Its Homogeneity

Abstract: Native speakers of English, Korean, and Malayalam (N = 30 in each group) rated their emotional reactions to stories describing events leading to anger, fear, sadness, and disgust. Speaker's language had no significant effect for anger, fear, and sadness stories, but did for disgust stories. The category named by the English word disgust includes emotional reactions to distaste, pathogen-containing substances, blood, sex, and moral violations. The category named by disgust's translations into Korean and Malayal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 29 publications
(37 reference statements)
1
16
0
Order By: Relevance
“…Similarly, there was also a cultural difference in the relation between contempt or anger and immorality: Both for Americans and Japanese, anger word, contempt word, and anger face were significantly correlated with immorality rating, whereas for Indians, only anger word was significantly correlated with immorality. Such findings signal cultural differences in the use of emotion concepts and demands more detailed attention (see Han et al, ; Kayyal & Russell, ; Kollareth & Russell, ).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Similarly, there was also a cultural difference in the relation between contempt or anger and immorality: Both for Americans and Japanese, anger word, contempt word, and anger face were significantly correlated with immorality rating, whereas for Indians, only anger word was significantly correlated with immorality. Such findings signal cultural differences in the use of emotion concepts and demands more detailed attention (see Han et al, ; Kayyal & Russell, ; Kollareth & Russell, ).…”
Section: Resultsmentioning
confidence: 98%
“…The words used for anger, contempt, sadness, fear and happiness in Malayalam were deshyam, pucham, sankadam, bhayam and santhosham , respectively. These Malayalam words were found to be translation equivalents of their respective English words (Han, Kollareth, & Russell, ; Kollareth & Russell, ). Those words in Japanese used in the present study were ikari, keibetsu, kanashimi, osore and yorokobi respectively, which were also reported to be equivalent to English words (Russell, Russell, Suzuki, & Ishida, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second study avoided this issue by using unlabeled arrays of facial expressions, but its generalizability is limited by the fact that (like the first study) it was conducted in the United States. Language groups differ in the degree to which they use the same word (e.g., "disgust") to describe reactions to both pathogen cues and acts that are morally condemned (Han, Kollareth, & Russell, 2016), and relations between facial expressions of disgust and responses to moral violations might similarly be nation-specific.…”
Section: Disgust Anger and Aggression: Further Tests Of The Equivalmentioning
confidence: 99%
“…The lack of homogeneity also has clear implications when it comes to translating emotion concepts (overview by Russell, 1991 ; see also Mesquita and Frijda, 2011 ). A recent study by Han et al (2015) showed that English speakers use the word ‘disgust’ to refer to distaste, pathogen-containing substances, blood and injury, inappropriate sexual events, and moral violations. In contrast, Korean speakers use the translation of ‘disgust’ only to refer to some of them (i.e., distaste, pathogen-containing substances, as well as blood and injury), while the translation equivalent in Malayalam does not refer to any of them.…”
Section: Introductionmentioning
confidence: 99%